Social security of an individual – assumptions and Polish reality: research findings (Economic and Political Thought, 2016)
Social security of a subject as an individual is not discussed in literaturein the way that makes it possible to categorise concepts and identify theachieved state of development and, as a result, use them in public policies.The concept of security presented in the report has been placed on the mapof social security and, with respect to scientific disciplines, is a matter ofpolitical studies, social studies, economics and sociology. Such a broad methodologicalplacement results from the adopted catalogue of indicators anddiscussed issues. The leitmotif of the analysis is determined by the relationbetween an individual and goods that are recognised as fundamental for thefunctioning of the society and meeting the needs of a man, an employee anda family. The research findings let the author verify the assumptions withregard to the epistemological component as well as social reality. However,he sees the need to develop a social perspective within the studies of securityand, in the practical dimension, the whole range of dependence of the socialand economic development determining individual social security.